THE INFLUENCE OF BRAND EQUITY, PRICES AND PROMOTIONS ON LIFESTYLE MEDIATED PURCHASE DECISIONS - Hardani Hardani; Aris Kurniawan; Lady Diana Warpindyastuti (Jurnal Scientia, 2023)
This research aims to investigate the influence of brand equity, price and promotion on the purchasing decisions of Starbucks consumers in Jakarta by mediating the role of lifestyle. The research method used is a cross-sectional design with a quantitative approach. Data was collected through a survey with structured questions distributed to 100 Starbucks consumer respondents who met the inclusion criteria. Data collection was carried out in June 2023 using the purposive sampling method. Data was collected online via the Gform survey platform, and data analysis was carried out using the Structural Equation Modeling (SEM) method via SmartPLS 3.00 software. The research results show that brand equity, price, and promotion influence purchasing decisions differently. As a mediator, lifestyle is proven to positively contribute to the relationship between the independent and dependent variables. This research contributes to understanding the factors that influence cafe consumers' purchasing decisions by highlighting the critical role of lifestyle as a mediator. The managerial implications of this research finding can help Starbucks and similar companies to optimize their marketing strategies, maintain brand image, and accommodate changes in consumer preferences.